Preliminary Lithic Analysis from the El Castillo Archaeological Site (Las Chapas, Chubut, Argentine Patagonia) - Schuster, Veronica (2022)
We present the results obtained from the lithic studies of the archaeological findings from the El Castillo site (Chubut, Argentine Patagonia), which show a predominance of the use of local raw materials – mainly xylopal and chalcedony – for the manufacture of an expeditious technology composed of natural-edged and multipurpose tools, as well as for the elaboration of formatted artifacts.